78.8k views
5 votes
Given x=-3, y=6, and z=-4 22-3y+4x=​

2 Answers

4 votes

Answer:

-8

Explanation:

Subsitute the variable "y" with 6 and the variable "x" with -3. Once the variables are replaced with the right numbers, the equation should read 22- 3(6) +4(-3). Using PEMDAS (parentheses, exponents, multiplication, division, addition, subtraction) you should do what's in the parentheses first. -3 times 6 is -18 and 4 times -3 is -12. 22-18-12= -8

User Riaz Laskar
by
4.5k points
6 votes

Answer: -8

Explanation: It's a good idea to get into the habit of using parenthses

when substituting numbers in for variables.

Since x = -3 and y = 6, 22 - 3y + 4x is 22 - 3(6) + 4(-3).

3(6) is 18 so we have 22 - 18 + 4(-3).

4(-3) is - 12 so we have 22 - 18 + -12.

Now, 22 - 18 is 4 and 4 + -12 is -8.

User Alex Kapranoff
by
4.5k points